Bio removal of Some Heavy metals by use Bacillus cereus - Noor Ali Mohammed; hazim abed walli Walli (Al-Qadisiyah Journal of Pure Science, 2020)
Abstract Four samples were collected from different agricultural soils, as the isolates were isolated from these samples, namely Bacillus cereus, which were identified based on phenotypic characteristics and molecular diagnosis. The bioremoval process was carried out using Bacillus cereus and cadmium at concentrations (0.5, 0.2, 0.1 mg) at a temperature of 37 ° C and pH 7 for a period (72,48,24 hours), as the results showed that the highest removal of cadmium was 86% at a concentration of 0.1 mg / ml and the lowest removal was 34% at a concentration of 0.5 mg / ml. This study included the effect of the incubation period on removing heavy element ions, and it was found that the best period was 24 hours compared to 72 and 48 hours .